Molecular and behavioral differentiation among Brazilian populations of Lutzomyia longipalpis (Diptera: Psychodidae: Phlebotominae). - Alejandra S Araki; Felipe M Vigoder; Luiz G S R Bauzer; Gabriel E M Ferreira; Gabriel E M Ferreira; Nataly A Souza; Izeneide B Araújo; James G C Hamilton; James G C Hamilton; Reginaldo P Brazil; Alexandre A Peixoto (Public Library of Science (PLoS), 2009)
Background Lutzomyia longipalpis is the primary vector of American visceral leishmaniasis. There is strong evidence that L. longipalpis is a species complex, but until recently the existence of sibling species among Brazilian populations was considered a controversial issue. In addition, there is still no consensus regarding the number of species occurring in this complex. Methodology/principal findings Using period, a gene that controls circadian rhythms and affects interpulse interval periodicity of the male courtship songs in Drosophila melanogaster and close relatives, we analyzed the molecular polymorphism in a number of L. longipalpis samples from different regions in Brazil and compared the results with our previously published data using the same marker. We also studied the male copulation songs and pheromones from some of these populations. The results obtained so far suggest the existence of two main groups of populations in Brazil, one group representing a single species with males producing Burst-type copulation songs and cembrene-1 pheromones; and a second group that is more heterogeneous and probably represents a number of incipient species producing different combinations of Pulse-type songs and pheromones. Conclusions/significance Our results reveal a high level of complexity in the divergence and gene-flow among Brazilian populations of the L. longipalpis species complex. This raises important questions concerning the epidemiological consequences of this incipient speciation process.